On banking regulation and lobbying - Hans Gersbach; Stylianos Papageorgiou (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
We study the political economy of bank capital regulation from a positive and normative perspective. In a general equilibrium setting, capital requirements and lobbying contributions are determined as the outcome of bargaining between banks and politicians. We show that bankers and politicians agree on lobbying contributions and capital regulation that renders banks fragile, reducing efficiency and fairness. Consideration of all general equilibrium effects, or a bail-in provision and high capital regulation standards from international agreements eliminate lobbying incentives, yielding an efficient and fair allocation.
Keywords: D53; D72; G21; G28; 330; Banking regulation; lobbying; regulatory capture; capital requirements; bank resolution; risk-taking